2008
DOI: 10.1088/0022-3727/41/18/185410
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric characterization of a ferroelectric film in the sub-GHz region

Abstract: A new method is proposed for the measurement of the dielectric properties of BaxSr1−xTiO3 (BST) thin films in the frequency range 106–1.8 × 109 Hz. A co-planar waveguide (CPW) transmission line was employed for impedance measurements via on-wafer probing. The measured impedance of the CPW line was found as a function of the probing position on the line. A simplified model of the CPW line under test allows the intrinsic dielectric properties of BST thin films to be extracted from the measured position-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…is the total thickness of the multilayer structure, E A and E B are theoretical electric fields of layers A and B, respectively. It can be noticed from Eq (4) and 5that the dielectric layers with lower permittivity (BZT thin films in this case)…”
Section: Capacitance (F)mentioning
confidence: 80%
“…is the total thickness of the multilayer structure, E A and E B are theoretical electric fields of layers A and B, respectively. It can be noticed from Eq (4) and 5that the dielectric layers with lower permittivity (BZT thin films in this case)…”
Section: Capacitance (F)mentioning
confidence: 80%
“…Metal-insulator-metal ͑MIM͒ capacitors are preferred to interdigital capacitors both for varactor devices and test structures, as these have lower operating voltages. Bao et al 15 and Suzuki et al 16 reported the use of one-port reflection measurements of MIM capacitors for characterization of ferroelectric varactors, including short de-embedding structures, but both these are prone to contact resistance or probe dependency problems which have significant impact on measurement errors. 17 According to Cramer et al 18 and Zhu et al, 19 two-port measurement techniques can overcome these limitations, but the configurations they have used have limitations themselves.…”
Section: Design and Simulation Of High Frequency Test Structuresmentioning
confidence: 99%
“…It is widely accepted that the control of the film stoichiometry, particular the A/B ratio in the ABO 3 perovskite lattice, is a key challenge for the production of thin films. The control of stoichiometry depends on the deposition method . It has been demonstrated that the BST film composition strongly effects the dielectric properties like tunability and dielectric losses .…”
Section: Introductionmentioning
confidence: 99%